ヒガシドロンイングモードランド, セール・ロンダーネ サンチ チガク チョウサタイ ホウコク 2007-2008 (JARE-49) - 小山内, 康人; オサナイ, ヤスヒト; 豊島, 剛志; トヨシマ, ツヨシ; 馬場, 壮太郎; ババ, ソウタロウ; 外田, 智千; ホカダ, トモカズ; 中野, 伸彦; ナカノ, ノブヒコ; 阿部, 幹雄; アベ, ミキオ; et al. (2008)
P(論文) 第49次日本南極地域観測隊(JARE-49)夏隊・セール・ロンダーネ山地地学調査隊は,ドロンイングモードランド航空ネットワークを利用して航空機で日本から直接南極内陸山地に赴き,2007年11月23日～2008年2月5日の75日間,キャンプ生活を送りながらスノーモービルと徒歩によりセール・ロンダーネ山地中央部地域の地質学的野外調査を実施した.また,ベルギー基地,インド基地等を訪問し,国際交流を実施した.今回の野外調査は,航空機を利用した南極内陸地域野外調査の初の試みであり,2007年度にスタートした国際極年(IPY)とも連動した国立極地研究所の一般プロジェクト研究(課題番号P-5-1:代表・本吉洋一)の初年度調査でもある.本報告では,設営面での計画の立案・準備から実施経過に至る過程について詳しく述べる. The Sør Rondane Mountains field research party, part of the summer party of the 49th Japanese Antarctic Research Expedition (JARE-49), carried out geological field work in the central part of the Sør Rondane Mountains and improved international goodwill with Belgian, Indian and other national expeditions for 75 days from November 23, 2007 to February 5, 2008. The field party tried to access the Sør Rondane Mountains directly from Japan by using the Dronning Maud Land Air Network (DROMLAN), which is the first attempt at an Antarctic inland field survey just using an airplane through the 50 years of JARE history. This research expedition was linked together with the International Polar Year and also the first operation program of a research project of National Institute of Polar Research (No. P-5-1: leader, Y. Motoyoshi). This report gives the details on the operation planning and a summary of the fieldwork including logistics and weather report. departmental bulletin paper